Leaders with many traits but a singular purpose: Lee Kuan Yew and Mahathir Mohamad - Hossain , Ishtiaq (IIUM, 2011)
During their long tenure as Prime Ministers of Singapore (from 1959 to 1990 for LKY) and Malaysia (from 1981 to 2003 for Dr. Mahathir), both leaders exercised singular influences over public policies in their respective countries, whether it is meritocracy in the case of ingapore or Malaysia‟s handling of the Asian Economic Crisis of 1997.This article argues that they be categorized as nation-builders.